2002
DOI: 10.1161/01.res.0000030179.78135.fa
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Involvement in the Adaptation to Altered Mechanical Load in Developing Chick Myocardium

Abstract: Abstract-Mechanical load regulates ventricular growth, function, and structure from the earliest stages of cardiac morphogenesis through senescence. Dramatic changes in cardiac form and function have been defined for developing cardiovascular systems, and changes in mechanical loading conditions can produce structural malformations such as left heart hypoplasia. To date, relatively little is known regarding the interactions between changes in mechanical load, morphogenesis, and the material properties of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 73 publications
(98 reference statements)
0
24
0
Order By: Relevance
“…In contrast, the hypertrophic response in these cells was found not to be dependent upon an intact microtubule cytoskeleton by Sadoshima et al [61]. In contrast to findings in adult hearts (see below), Schroder et al [64] observed that unloading the embryonic ventricle in chicks increased microtubule density, the reason for this different response in embryonic hearts is unknown. Hypoosmotic swelling has been shown to disrupt microtubules in neonatal cells, though neither taxol nor colchicine affected volume regulation [41].…”
Section: Responses Of Microtubules To Mechanical Stimulationmentioning
confidence: 78%
“…In contrast, the hypertrophic response in these cells was found not to be dependent upon an intact microtubule cytoskeleton by Sadoshima et al [61]. In contrast to findings in adult hearts (see below), Schroder et al [64] observed that unloading the embryonic ventricle in chicks increased microtubule density, the reason for this different response in embryonic hearts is unknown. Hypoosmotic swelling has been shown to disrupt microtubules in neonatal cells, though neither taxol nor colchicine affected volume regulation [41].…”
Section: Responses Of Microtubules To Mechanical Stimulationmentioning
confidence: 78%
“…4,12,33 Dynamic microtubules are crucial for modulating cell motility, 5 and the adaptation of cell to vary of mechanical level. 27 Microtubule destabilization significantly enhanced aspects of their motility. 5 Acetylation plays a role in the maintenance of stable populations of microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…After clipping, ventricular contractility development may lag behind as a consequence of impaired cardiac development. Mechanical load regulates ventricular growth (30,31). Venous obstruction temporarily reduces mechanical load on the myocardium and thus probably slows down the ventricular growth and differentiation process (3).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diastolic function may be a critical regulatory pathway during cardiac morphogenesis (34). Recently Schroder et al (31) found an increase in microtubule density and ␤-tubulin protein after reduced mechanical load in the stage 27 embryonic heart after left atrial ligation at stage 21. They observed increased myocardial stiffness in response to reduced mechanical load.…”
Section: Discussionmentioning
confidence: 99%